A case of a large colonic lipoma resected by endoscopic submucosal dissection: A long‐term endoscopic observation. Issue 3 (7th September 2017) - Lin, Jung‐Chun; Chen, Peng‐Jen; Shih, Yu‐Lueng; Chang, Yi‐Ming; Chang, Wei‐Kuo; Hsieh, Tsai‐Yuan
Summary: Gastrointestinal (GI) lipomas are benign, slow‐growing subepithelial tumors, and are most commonly found in the colon. No intervention is needed for smaller or asymptomatic lipomas. Endoscopic removal or surgery is reserved for larger lesions. However, whether endoscopic submucosal dissection (ESD) is a suitable method for the treatment of a large submucosal lipoma of the colon has long been controversial. In addition, less is known regarding the long‐term prognosis of patients undergoing the ESD on large colonic lipomas. In this report, we present the case of a 67‐year‐old man who presented with abdominal pain and was diagnosed with a large colonic lipoma. Standard ESD was performed to remove the lipoma. During the follow‐up period of 7 years, no recurrence was observed. ESD is another option for the treatment of large colonic lipomas with an excellent long‐term prognosis. Copyright © 2017, The Gastroenterological Society of Taiwan, The Digestive Endoscopy Society of Taiwan and Taiwan Association for the Study of the Liver.